Impact of GLP-1 Receptor Agonists on Psoriasis and Cardiovascular Comorbidities: A Narrative Review - Haran K; Johnson CE; Smith P; Venable Z; Kranyak A; Bhutani T; Jeon C; Liao W (Dove Medical Press, 2024)
Kathryn Haran,1 Chandler E Johnson,1 Payton Smith,1 Zoë Venable,2 Allison Kranyak,1 Tina Bhutani,1 Caleb Jeon,2 Wilson Liao1,3 1Department of Dermatology, University of California San Francisco, San Francisco, CA, USA; 2Department of Dermatology, Golden State Dermatology, Berkeley, CA, USA; 3Institute for Human Genetics, University of California San Francisco, San Francisco, CA, USACorrespondence: Wilson Liao, Department of Dermatology, University of California San Francisco, 2340 Sutter Street, Box 0808, San Francisco, CA, 94143, USA, Tel +1 415 476-8364, Email wilson.liao@ucsf.eduAbstract: Psoriasis is an immune-mediated skin disease known to be associated with a higher risk of cardiometabolic comorbidities such as hypertension, myocardial infarction, and stroke. GLP-1 receptor agonists (GLP-1RAs) are medications approved to treat type 2 diabetes mellitus and obesity and have been reported to improve psoriasis. As more psoriasis patients start GLP-1RAs for approved indications, it is of interest to understand the impact of GLP-1RAs on both psoriasis and associated cardiovascular risk. In this review, we examine the effect of GLP-1RAs on psoriasis and cardiovascular comorbidities-defined as hypertension, stroke, and myocardial infarction. The majority of case reports and prospective cohort studies found GLP-1RAs improved psoriasis, while two randomized controlled trials showed conflicting results. For cardiovascular disease, most studies found GLP-1RAs reduced systolic blood pressure, total stroke, and myocardial mortality. These results suggest that GLP-1RAs may be a particularly promising treatment for psoriasis patients with diabetes or obesity comorbidities, offering both cardioprotective benefits and potential improvement in psoriatic symptoms.Keywords: skin disease, oxidative stress, hypertension, stroke, myocardial infarction